2009
DOI: 10.1210/en.2008-0757
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Stress Inhibits Amplitude of Gonadotropin-Releasing Hormone Pulses Independent of Cortisol Action on the Type II Glucocorticoid Receptor

Abstract: Our laboratory has developed a paradigm of psychosocial stress (sequential layering of isolation, blindfold, and predator cues) that robustly elevates cortisol secretion and decreases LH pulse amplitude in ovariectomized ewes. This decrease in LH pulse amplitude is due, at least in part, to a reduction in pituitary responsiveness to GnRH, caused by cortisol acting via the type II glucocorticoid receptor (GR). The first experiment of the current study aimed to determine whether this layered psychosocial stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 44 publications
0
38
2
Order By: Relevance
“…The interaction between stress hormones and reproductive function has been known for many years (for reviews, see [36,37]). Although the mechanism by which the hypothalamic-pituitary-adrenal axis modifies the function of the hypothalamic-pituitary-gonadal (HPG) axis is not completely understood, stress hormones can act at all levels of the HPG axis [38][39][40][41][42]. High glucocorticoid levels cause decreased LH pulse frequency and increased amplitude [43].…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between stress hormones and reproductive function has been known for many years (for reviews, see [36,37]). Although the mechanism by which the hypothalamic-pituitary-adrenal axis modifies the function of the hypothalamic-pituitary-gonadal (HPG) axis is not completely understood, stress hormones can act at all levels of the HPG axis [38][39][40][41][42]. High glucocorticoid levels cause decreased LH pulse frequency and increased amplitude [43].…”
Section: Discussionmentioning
confidence: 99%
“…Breen et al (2005) found a decrease in LH pulses after administration of 30 ng/mL cortisol in sheep. This effect on LH release is also a result of a reduced GnRH pulse amplitude (Wagenmaker et al 2009). Moreover, Edwards et al (1987) observed that heifers subjected to transport stress followed by superovulation reached high cortisol concentrations and had decreased corpus luteum production.…”
Section: Discussionmentioning
confidence: 99%
“…We have determined that psychosocial stress inhibits pulsatile LH secretion in ovariectomized sheep by reducing both gonadotropin-releasing hormone (GnRH) pulse amplitude [16] and pituitary responsiveness to GnRH [17]. Although the suppression of pulsatile GnRH secretion is independent of cortisol action [16], inhibition of pituitary responsiveness is caused by the concurrent rise in plasma cortisol [17].…”
Section: Introductionmentioning
confidence: 99%